Encyclopaedia of eukaryotic DNA methylation: from patterns to mechanisms and functions. (30th June 2022) - Sarkies, Peter
Abstract : DNA methylation is an epigenetic modification with a very long evolutionary history. However, DNA methylation evolves surprisingly rapidly across eukaryotes. The genome-wide distribution of methylation diversifies rapidly in different lineages, and DNA methylation is lost altogether surprisingly frequently. The growing availability of genomic and epigenomic sequencing across organisms highlights this diversity but also illuminates potential factors that could explain why both the DNA methylation machinery and its genome-wide distribution evolve so rapidly. Key to this are new discoveries about the fitness costs associated with DNA methylation, and new theories about how the fundamental biochemical mechanisms of DNA methylation introduction and maintenance could explain how new genome-wide patterns of methylation evolve.